Improving the stability and inertness of Cu(ii) and Cu(i) complexes with methylthiazolyl ligands by tuning the macrocyclic structure. Issue 17 (4th April 2016) - Le Fur, Mariane; Beyler, Maryline; Le Poul, Nicolas; Lima, Luís M. P.; Le Mest, Yves; Delgado, Rita; Platas-Iglesias, Carlos; Patinec, Véronique; Tripier, Raphaël
Abstract : A tacn bearing methylthiazolyl arms was synthesized and its copper(ii ) and (i ) complexes showed excellent stability and inertness in aqueous medium. Abstract : A tacn based ligand bearing two methylthiazolyl arms (no2th ) was synthesized with the aim to find ligands forming very stable and inert complexes with Cu(ii ) and Cu(i ) in aqueous medium for radiopharmaceutical applications. Theno2th ligand was efficiently prepared following the orthoamide intermediate synthesis. The complexes with Cu 2+ and Zn 2+ were obtained and analyzed by X-ray diffraction. The [Cu(no2th )] 2+ complex presents a pentacoordinated distorted square pyramidal coordination geometry, while the metal ion in [Zn(no2th )] 2+ adopts a hexacoordinated distorted trigonal prismatic geometry involving the coordination of a perchlorate counter ion. The acid–base properties ofno2th have been studied using potentiometric titrations, and the stability constants of Cu 2+ and Zn 2+ complexes were determined by potentiometric and UV-vis titrations using H4 edta as a competitor ligand. The stability constant determined for the Cu 2+ complex is rather high (log  K CuL = 20.77 and pCu = 17.15), and moreoverno2th exhibits a high selectivity for copper(ii ) in relation to zinc(ii ). The kinetics of the copper(ii ) complexation process is very fast even in acidic medium. In addition, the [Cu(no2th )] 2+ complex was found to be inert under rather harsh conditions (up to 2 M HCl and 60 °C), displaying a very high half-life time of about 15 days in 2 M HCl at 90 °C. The electrochemical reduction of the copper(ii ) complex in water leads to the reversible formation of a stable copper(i ) species. Spectroscopic studies performed by NMR, UV-vis and EPR, assisted by theoretical calculations, show that the [Cu(no2th )] 2+ complex presents a structure in solution similar to that observed in the solid state. When compared to its cyclam di- N -methylthiazolyl counterpart, the results reported in this paper unambiguously show that replacing the cyclam unit by a tacn moiety improves the stability and inertness of its Cu(ii ) and Cu(i ) complexes.